Patient Reflections on Decision Making for Laryngeal Cancer Treatment. (February 2017) - Shuman, Andrew G.; Larkin, Knoll; Thomas, Dorothy; Palmer, Frank L.; Fins, Joseph J.; Baxi, Shrujal S.; Lee, Nancy; Shah, Jatin P.; Fagerlin, Angela; Patel, Snehal G.
Objective: To describe the reflections of patients treated for laryngeal cancer with regard to treatment-related decision making. Study Design: Cross-sectional survey-based pilot study. Setting: Single-institution tertiary care cancer center. Subjects/Methods: Adults with laryngeal carcinoma were eligible to participate (N = 57; 46% treated surgically, 54% nonsurgically). Validated surveys measuring decisional conflict and regret explored patients' reflections on their preferences and priorities regarding treatment-related decision making for laryngeal cancer and how patient-reported functional outcomes, professional referral patterns, and desired provider input influenced these reflections. Results: When considering the level of involvement of surgeons, radiation oncologists, and medical oncologists in their care, patients were more likely to believe that the specialist whom they saw first was the most important factor in deciding how to treat their cancer (Fisher's exact, χ 2 = 16.2, df = 6, P = .02). Patients who were treated for laryngeal cancer who reported worse voice-related quality of life recalled more decisional conflict ( P = .01) and experienced more decisional regret ( P < .001). Of the patients for whom speech was a top priority prior to treatment, better voice-related quality of life overall scores were correlated with less decision regret about treatment decisions ( P < .02). Of the patients for whom eating and drinking were top priorities prior to treatment, better MD Anderson Dysphagia Inventory global scores were correlated with less decision regret about treatment decisions ( P < .002). Conclusion: Patient priorities and attitudes, coupled with functional outcomes and professional referral patterns, influence how patients reflect on their choices regarding management of laryngeal cancer. Better understanding of these variables may assist in ensuring that patients' voices are integrated into individualized laryngeal cancer treatment planning.